2016
DOI: 10.1080/08957959.2016.1198905
|View full text |Cite
|
Sign up to set email alerts
|

Combined single crystal polarized XAFS and XRD at high pressure: probing the interplay between lattice distortions and electronic order at multiple length scales in highTccuprates

Abstract: Some of the most exotic material properties derive from electronic states with short correlation length (∼10-500Å), suggesting that the local structural symmetry may play a relevant role in their behavior. Here we discuss the combined use of polarized x-ray absorption fine structure and x-ray diffraction at high pressure as a powerful method to tune and probe structural and electronic orders at multiple length scales. Besides addressing some of the technical challenges associated with such experiments, we illu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The increased thermal Debye–Waller factors at higher temperatures cause the small reductions in the amplitudes of the spectral features. Although the EXAFS spectra of SCO show the expected features from the nearest-neighbor O, Sr, and Cu, it differs from that of the La 2 CuO 4 family ( 37 , 47 ) since the spectra originate in the structures along the a axis and in the bc plane. In contrast to the expected behavior demonstrated by the YSCO-Mo spectra, the E || a spectra of SCO are complicated, showing a large reduction with increasing temperature for the Cu-O feature and an anomalous diminution of the Sr modulus amplitude with decreasing temperature ( Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The increased thermal Debye–Waller factors at higher temperatures cause the small reductions in the amplitudes of the spectral features. Although the EXAFS spectra of SCO show the expected features from the nearest-neighbor O, Sr, and Cu, it differs from that of the La 2 CuO 4 family ( 37 , 47 ) since the spectra originate in the structures along the a axis and in the bc plane. In contrast to the expected behavior demonstrated by the YSCO-Mo spectra, the E || a spectra of SCO are complicated, showing a large reduction with increasing temperature for the Cu-O feature and an anomalous diminution of the Sr modulus amplitude with decreasing temperature ( Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Although we have found that the excess O in YSCO-Mo is mostly taken up by domains enriched in octahedral Mo(VI) substituting in the Cu(1) chains, much of the extra charge resides in the CuO 2 planes ( 27 ) and some of the carriers constitute a normal Fermi liquid that coexists with the superconductivity ( 26 ). The inherent inhomogeneity ( 37 ) in YSCO-Mo and SCO was probed by EXAFS, which is arguably the most incisive experimental method for characterizing short-range order and is especially sensitive to its changes. Diffraction patterns originate in the long-range average structure of a material and provide precise information on the symmetry and symmetry-constrained locations of the atoms that dominate the Bragg peaks.…”
mentioning
confidence: 99%
“…A procedure that was key in these studies was the enhancement of the sensitivity of EXAFS to the different components of the structure (38) by orienting the samples in a magnetic field to align them along a unique crystallographic axis. The spectra therefore measure the projections of the neighbor atoms on the axis parallel to the orienting magnetic field and the plane perpendicular to it, rendering the problem one of cylindrical symmetry.…”
mentioning
confidence: 99%
“…structural order is not essential for CO to appear. Follow-up studies found that CO persists up to ≈3 GPa, but in the presence of local LTT lattice deformations [6,7].…”
mentioning
confidence: 99%
“…Similarly ambiguous connection of CO/SO to the structure is also seen in rare-earth doped La214 systems, where CO forms close to the LTO/LTT transition but with different onset temperatures. However, although these systems appear similar, upon closer inspection of their pressure-controlled phase diagrams, it becomes apparent how different they are compared to LBCO [4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%